2020
DOI: 10.1126/sciadv.aax7989
|View full text |Cite
|
Sign up to set email alerts
|

Flavivirus induces and antagonizes antiviral RNA interference in both mammals and mosquitoes

Abstract: Mosquito-borne flaviviruses infect both mammals and mosquitoes. RNA interference (RNAi) has been demonstrated as an anti-flavivirus mechanism in mosquitoes; however, whether and how flaviviruses induce and antagonize RNAi-mediated antiviral immunity in mammals remains unknown. We show that the nonstructural protein NS2A of dengue virus-2 (DENV2) act as a viral suppressor of RNAi (VSR). When NS2A-mediated RNAi suppression was disabled, the resulting mutant DENV2 induced Dicer-dependent production of abundant DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 46 publications
2
60
0
2
Order By: Relevance
“…Distinct positive-and negative-strand RNA viruses from the Flaviviridae, Nodaviridae, Orthomyxoviridae, and Picornaviridae induce Dicer-mediated production of vsiRNAs and encode unrelated dsRNA-binding VSRs to suppress the biogenesis of cognate vsiRNAs in mammalian cells (10,(12)(13)(14)(15). Results from this work provide several important insights into the mechanism and function of the new mammalian antiviral response.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Distinct positive-and negative-strand RNA viruses from the Flaviviridae, Nodaviridae, Orthomyxoviridae, and Picornaviridae induce Dicer-mediated production of vsiRNAs and encode unrelated dsRNA-binding VSRs to suppress the biogenesis of cognate vsiRNAs in mammalian cells (10,(12)(13)(14)(15). Results from this work provide several important insights into the mechanism and function of the new mammalian antiviral response.…”
Section: Discussionmentioning
confidence: 88%
“…Mammalian antiviral RNAi has been documented during infection of either undifferentiated cells with wild-type viruses or differentiated cells and mice with mutant viruses rendered defective in RNAi suppression (10)(11)(12)(13)(14)(15). However, previous studies have shown that a range of wild-type RNA viruses do not trigger production of a dominant peak of vsiRNAs in several commonly used lines of mature mammalian cells or replicate to higher levels in human 293T cells upon Dicer inactivation (15,(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a countermeasure, viruses encode viral suppressors of RNAi (VSRs) to antagonize the RNAi pathway at different steps. For example, Influenza A virus (IAV) NS1, human enterovirus A71 (EV-A71) 3A and Dengue virus 2 (DENV2) NS2A have been identified to act as VSRs to inhibit vsiRNA production and antiviral RNAi response in the context of viral infections (Qiu et al, 2020;Ding et al, 2018). Thus, the understanding of how SARS-CoV-2 interacts with antiviral RNAi is important for the better knowledge of this novel coronavirus, and may contribute to the efforts of controlling the spread of infections and developing effective therapies.…”
mentioning
confidence: 99%